2009
DOI: 10.1007/s11547-009-0462-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose saving through the use of cone-beam CT in hearing-impaired patients

Abstract: Owing to low radiation dose and sufficient image quality, CBCT could be considered an adequate technique for postoperative imaging and follow-up of patients with bionic ear implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Successful identification of the CI electrode scalar position has also been reported in temporal bone studies [Husstedt et al, 2002;Ruivo et al, 2009;Cushing et al, 2012;Saeed et al, 2014] and in vivo postoperative studies [Aschendorff et al, 2007]. Another important advantage of FPV CT for in vivo applications is that it offers reduced exposure to ionizing radiation compared to conventional helical high-resolution computed tomography [Faccioli et al, 2009;Ruivo et al, 2009].…”
Section: Introductionmentioning
confidence: 87%
“…Successful identification of the CI electrode scalar position has also been reported in temporal bone studies [Husstedt et al, 2002;Ruivo et al, 2009;Cushing et al, 2012;Saeed et al, 2014] and in vivo postoperative studies [Aschendorff et al, 2007]. Another important advantage of FPV CT for in vivo applications is that it offers reduced exposure to ionizing radiation compared to conventional helical high-resolution computed tomography [Faccioli et al, 2009;Ruivo et al, 2009].…”
Section: Introductionmentioning
confidence: 87%
“…[17][18][19][20][21][22][23] When evaluating the CT scan, several points need to be considered. An axial plane view CT scan, imaging the mastoid portion of the facial nerve, should be included as well as a coronal view, which is especially necessary in patients with malformations.…”
Section: Preoperative Radiological Assessmentmentioning
confidence: 99%
“…Faccioli et al (15) found that the effective dose of CBCT was almost 3 times less than MSCT. Ruivo et al (16) argued that CBCT provides equivalent information to 16-slice CT in temporal bone imaging, with a significant reduction in effective radiation dose.…”
Section: Discussionmentioning
confidence: 99%